Assessment of aneuploidy formation in human blastocysts resulting from donated eggs and the necessity of the embryos for aneuploidy screening - Haddad, Ghassan (J Assist Reprod Genet, 2015)
PURPOSE: To examine the prevalence of aneuploidy in human blastocysts resulting from donated eggs and embryo implantation after transfer of normal euploid embryos. Also, to assess the necessity of preimplantation genetic screening (PGS) for embryos produced with donor eggs. METHODS: Blastocysts from donor-recipient cycles were biopsied for PGS (PGS group) and the samples were analyzed with DNA microarray. Euploid blastocysts were transferred to the recipients, and both clinical pregnancy and embryo implantation were examined and compared with embryos without PGS (control group). RESULTS: After PGS, 39.1 % of blastocysts were abnormal, including aneuploidy and euploid with partial chromosome deletion and/or duplication. Transfer of normal euploid blastocysts brought about 72.4 % of clinical pregnancy, 65.5 % of ongoing/delivery and 54.9 % of embryo implantation rates; these rates were slightly higher than those in the control group (66.7, 54.0 and 47.8 %, respectively), but there was no statistical difference between the two groups. By contrast, the miscarriage rate was higher in the control group (19.2 %) than in the PGS group (9.5 %), but no statistical difference was observed. Transfer of two or more embryos did not significantly increase the ongoing/delivery rates in both groups, but significantly increased the twin pregnancy rates (50.0 % in the PGS group and 43.8 % in the control group). CONCLUSION(S): High proportions of human blastocysts derived from donor eggs are aneuploid. Although pregnancy and embryo implantation rates were increased, and miscarriage rates were reduced by transfer of embryos selected by PGS, the efficiency was not significantly different as compared to the control, suggesting that PGS may be necessary only in some specific situations, such as single embryo transfer.